THE ROLE OF EFFECTIVE COMMUNICATION AND PATIENT INVOLVEMENT IN IMPROVING THE QUALITY OF CARE DURING THE COVID 19 PANDEMIC - Hilda hilda, Yahya Thamrin, Alimin Maidin, Lalu Muhammad Saleh (Chelonian Research Foundation, 2023)
Background: Effective communication is an important factor in providing safe patient care. Communication failures in health care lead to serious medical errors that impact the quality of health care. Exposed patients experience psychological stress, work fatigue, fear and stigma, therefore effective communication is very important and must be carried out in the workplace. The aim of writing this literature review is to explain the role of effective communication between patients, families and health workers in improving the quality of health services during the Covid-19 pandemic. Method: This literature review was prepared by conducting a literature review of scientific articles published in the last 5 years, namely articles published from 2016 - 2021. The literature search was carried out on the PubMed, ScienceDirect and Google Scholar databases. The keywords used in the search are "effective communication", "quality of care". Results: An important strategy result during the COVID-19 pandemic is increasing the knowledge and skills of health workers in communicating with patients and families. Stress and fear arising from the pandemic are controlled with guidance and counseling from trusted doctors and health workers. Doctors and other health workers must be competent in effective consultation techniques. However, there are many factors that influence receiving information, such as social and cultural characteristics, gender, generation, language, beliefs, religion, and various other literacies. Conclusion: Understanding and practicing various communication strategies is very important for doctors and health workers to develop therapeutic relationships with COVID-19 patients. Communication can be done by utilizing technology to promote communication by integrating workstations with video conferencing software or adding communication via email and telephone is a solution strategy. Keywords: Effective Communication, Quality of Health Services, COVID 19 Pandemic